Multicultural Instructional Design 2020
DOI: 10.4018/978-1-5225-9279-2.ch015
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Teaching Competence in the Disciplines

Abstract: As universities continue to internationalize their curricula and recruit a growing number of international students, instructors facilitate learning in increasingly diverse classrooms. This chapter explores the application of Intercultural Teaching Competence (ITC) by faculty members across the disciplines at a large Canadian research university. Based on focus group interviews with instructors in eighteen disciplines, it provides varied and concrete examples of how instructors mobilize intercultural teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Faculty and staff play a pivotal role in achieving this goal by modeling intercultural competence and fostering inclusive learning environments. Research has shown that ICL-trained faculty and staff can significantly impact students' educational experiences and outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Faculty and staff play a pivotal role in achieving this goal by modeling intercultural competence and fostering inclusive learning environments. Research has shown that ICL-trained faculty and staff can significantly impact students' educational experiences and outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Teaching drama is essential for improving language communication [6]. Because drama is a resource in the foreign language classroom in promoting intercultural competence and developing an awareness of interpersonal dimension and drama also offers the foreign culture as well as conflict situations and emotions seldom encountered in textbook dialogues and materials, thus opening up to the students a world which is often denied to them in the foreign language classroom [7,8,10]. Furthermore, Drama subject is a media to develop students' awareness about their own culture and other cultures.…”
Section: Introductionmentioning
confidence: 99%